From accuracy to accountability: subjecting global indicators to the rule of law. Issue 4 (3rd January 2018) - Frydman, Benoit
Abstract: This paper presents a double genealogy of indicators as instruments of governance. These have their roots both in the use of statistical tools for normative purposes by states and in the development of indicators within firms as preferred instruments of 'new management'. The paper argues that social indicators not only convey information, but are genuine tools of global governance and that, for this reason, their legitimacy depends not only on their accuracy, but also on their accountability. If indicators are intended to produce or effectively produce regulatory effects, they should be subjected to the rule of law and to judicial review. The essay ends by formulating four main principles that these indicators should comply with.